Analisis Frekuensi Waktu pada Sinyal Jantung Koroner Menggunakan Distribusi Wigner Ville - Puspasari, Ira (Jurnal Informatika dan Sistem Informasi, 2015)
Coronary heart disease is the third leading cause of death each year and the number of patients with coronary heart disease growing. Due to the rise of the disease, we need a tool for early detection of heart abnormalities that coronary heart disease. For research on electronic detection, a preliminary study on cardiac signals is needed. Coronary Heart Disease has been explored with certain specifications, information on the frequency and time distribution by using Wigner - Ville and the result that the frequency detected of 200 Hz, which is the specification of coronary heart disease with left ventricular hypertrophy abnormal values obtained repolyzation characteristic frequency range between 200-550 Hz, and the time interval 50-100 ms, coronary heart disease with specifications lateral inferior infarct and ishemic has a value characteristic frequency range of 200-500 Hz and the time interval 50-150 ms, coronary artery infarct with inferior specifications, ishemic and sinus rhythm the initial frequency of ventricular complexes have characteristic value interval 20-350 Hz frequency and time interval 50-250 ms.